Surface ozone depletion at Syowa Station, Antarctica in 1997 spring season - Yuji Esaki; Naohiko Hirasawa; Masahiko Hayashi; Takashi Yamanouchi (National Institute of Polar Research, 2010)
Surface ozone concentration decreased dramatically from 28 to 29 August 1997 at Syowa Station, Antarctica. Aerosol concentrations with diameters of 0.01-5.0 μm increased to several times as much as background concentrations, accompanied with the surface ozone depletion. Air mass above Syowa Station in SOD events had high humidity and low ozone concentration. The SOD also accompanied change of wind direction, and the results of backward trajectory analysis suggested that this air mass was transported from the westerly sea ice area of a cold front within several days. These results suggested that the SOD on 28 29 August 1997 at Syowa Station occurred by transport of the air mass.